Self-reproduction as an autonomous process of growth and reorganization in fully abiotic, artificial and synthetic cells - Sai Krishna Katla; Chenyu Lin; Juan Pérez-Mercader (Proceedings of the National Academy of Sciences, 2025)
We investigate mechanisms for the observed nonlinear growth in the number of polymer vesicles generated during a photo-Reversible Addition-Fragmentation Chain Transfer-based polymerization-induced self-assembly (PISA) reaction. Our experimental results reveal the presence of a self-reproduction process during which chemically active polymer protocells are chemically and autonomously generated in a light-stimulated one-pot reaction that starts from a homogeneous blend of non-self-assembling molecules and which, as observed microscopically, form vesicular objects that grow and multiply (reproduce) during irradiation with green light (530 nm) as the reaction proceeds. By using a filtration-based protocol, our experiments demonstrate that the self-reproduction process occurs concomitantly with the PISA process and results in a nonlinear increase in the number of polymer vesicles during photopolymerization which can only be ascribed to their reproduction via polymeric spores ejected from previously existing first-generation vesicles. The second and subsequent generations’ vesicles also self-reproduce and continue the process of population growth.